Acute upper gastrointestinal bleeding: endoscopic assessment and treatment. (1st February 2020) - Patel, Rajan; Mann, Steven
Abstract : Acute upper gastrointestinal bleeding (AUGIB) represents 10% of medical emergencies in the UK and is associated with a significant mortality risk. Mortality has remained steady over the past 2 decades, at approximately 10%, with over 4000 deaths per annum in the UK. Patients with significant bleeding present with symptoms of haematemesis, melaena or haematochezia (rapid transit of red blood through the GI tract). An assessment of haemodynamic stability along with adequate resuscitation is vital prior to performing safe endoscopy. The performance of prompt upper gastrointestinal endoscopy is then necessary, as it has diagnostic, prognostic and therapeutic roles. Early identification of aetiology (variceal versus non-variceal bleeding) is important and directs endoscopic and medical treatment. An increasing number of endoscopic therapeutic options are now available.